Malignant perivascular epithelioid cell tumor (PEComa) arising in the broad ligament. Issue 5 (1st August 2004) - Fink, D.; Marsden, D. E.; Edwards, L.; Camaris, C.; Hacker, N. F.
Abstract : Malignant perivascular epithelioid cell tumor (PEComa) is an extremely rare mesenchymal neoplasm mostly composed of HMB-45-positive epithelioid cells with clear-to-eosinophilic cytoplasm, a propensity for perivascular distribution and a coexpression of smooth muscle markers. The uterus seems to be one of the most prevalent sites of involvement, although only 14 cases of uterine PEComa have been described. We report the case of a 51-year-old woman with a PEComa arising in the broad ligament. She was treated with total abdominal hysterectomy, bilateral salpingo-oophorectomy, omentectomy, and pelvic radiation, and remains without evidence of disease 15 months after diagnosis. This is, to the best of our knowledge, the first report of a malignant PEComa arising in the broad ligament. To correctly diagnose PEComa, an extensive immunohistochemical panel is essential. As PEComas can behave in an aggressive manner, careful follow-up is warranted.